Pulsed current activated synthesis and consolidation of nanostructured MoSi2-TaSi2 composite - Park, Na-Ra; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Hyun-Kuk; Shon, In-Jin (SPRINGER, 2013)
Nanopowders of Mo, Ta, and Si were fabricated by high-energy ball milling. A dense nanostructured MoSi2-TaSi2 composite was simultaneously synthesized and sintered by the pulsed current activated heating method within 5 min from mechanically activated powder of Mo, Ta, and Si. A highly-dense MoSi2-TaSi2 composite was produced under simultaneous application of an 80-MPa pressure and the pulsed current. The sintering behavior, mechanical properties, and microstructure of the composite were investigated.
Keywords: MECHANICAL-PROPERTIES; MOSI2-SIC COMPOSITE